Public Investment when Capital is Back - Distributional Effects of Heterogeneous Saving Behavior - Linus Mattauch; Ottmar Edenhofer; David Klenert; Sophie Bénard (Center for Economic Studies and ifo Institute (CESifo), 2014)
We study the impact of heterogeneous saving behavior on the distributional effects of public investment. A capital tax is levied to finance productive public capital in an economy with two types of households: high income households who save dynastically and middle income households who save for retirement. We find that inequality is reduced the higher the capital tax rate and that low rates even constitute a Pareto-improvement. There is thus no clear-cut trade-off between efficiency and inequality: middle income households' consumption is maximal at a higher capital tax rate than high income households' consumption.
Keywords: E60; H23; H31; H40; H54; 330; public capital; wealth disparity; inequality; household heterogeneity; Pasinetti Paradox; saving behavior